A solution for 5G indoor coverage - Hao XU; Chen LIU (Dianxin kexue)
Indoor coverage is a very important and difficult problem for 5G network deployment.By analyzing the technical characteristics of 5G massive MIMO systems and solutions to improve the performance of indoor coverage.The most important way which the outdoor macro cells were still for basic coverage was proposed,proved by theoretical analysis based on the field test results.By the meantime using digital indoor distribution system and small cells according to scenarios requirement can provide an all-round solution for indoor coverage.